The international law on climate change - Mayer, Benoit (Cambridge, United Kingdom : Cambridge University Press, 2018)
'Global climate change is a topic of continuously growing interest. As more international treaties come into force, media coverage has increased and many universities are now starting to conduct courses specifically on climate change laws and policies. This textbook provides a survey of the international law on climate change, explaining how significant international agreements have sought to promote compliance with general norms of international law.
Includes bibliographical references and index.
Keywords: Climatic changes -- Law and legislation; Global warming -- Law and legislation; Environmental law, International; International law